PRINSIP TANGGUNG JAWAB PENGELOLAAN BARANG MILIK NEGARA MENUJU GOOD GOVERNANCE - Agustina, Enny (Solusi, 2021)
State property or abbreviated as BMN is a state asset whose management must be regular and accountable in accordance with the prevailing laws and regulations and not in conflict with the rules and laws where the responsibility starts from the source or input, the process carried out, to the result or output. which is obtained. This study uses normative legal research or doctrinal legal research with a legal inventory approach, which collects norms that have been identified as legal norms. As normative legal research, the data source used is secondary data, consisting of primary, secondary and tertiary legal materials. Qualitative analysis of research data, namely comparing or applying applicable laws and regulations, the opinions of scholars (doctrines) and other legal theories. Research conclusions deductively, namely drawing conclusions starting from the general to the specific. The conclusion of this study is the law, binding regulations are considered very responsible for protecting state assets for the realization of good governance.